Pharmacological Effects of a Novel Recombinant Hirudin, CX-397, In Vivo and In Vitro: Comparison with Recombinant Hirudin Variant-1, Heparin, and Argatroban - Komatsu, Yasuhiko; Inoue, Yoshifumi; Goto, Yuso; Fukazawa, Tominaga; Hayashi, Hideya (Thrombosis and Haemostasis, 1999)
The novel recombinant hirudin analog CX-397 was investigated with respect to its pharmacological activity and antithrombin profiles in vivo and in vitro. In three different types of thrombosis models in rats, including stasis and thrombin-induced venous, glass surface-activated arterio-venous shunt, and ferric chloride-induced arterial thrombosis models, CX-397 and rHV-1 elicited potent antithrombotic effects, where the minimum effective doses of rHV-1 tended to be higher than those of CX-397 in the arterio-venous shunt and arterial thrombosis models. The hemorrhagic risk of CX-397 in template bleeding in rats was not higher than that of rHV-1, indicating that CX-397 is superior to rHV-1 for treating the platelet-dominant type of thrombosis. However, no differences were detected between CX-397 and rHV-1 in their effects on in vitro coagulation times and thrombin-induced platelet aggregation, suggesting the possibility that some unknown mechanisms other than simple thrombin inhibition are also involved in their anti-thrombotic actions.